44.2k views
4 votes
How do I convert Y= x^2 + 3x + 1 into vertex form?

User Yadnesh
by
5.8k points

1 Answer

4 votes

Answer:

y = (x +
(3)/(2) )² -
(5)/(4)

Explanation:

The equation of a parabola in vertex form is

y = a(x - h)² + k

where (h, k) are the coordinates of the vertex and a is a multiplier

To obtain this form use the method of completing the square.

Given

y = x² + 3x + 1

add/ subtract ( half the coefficient of the x- term )² to x² + 3x

y = x² + 2(
(3)/(2) )x +
(9)/(4) -
(9)/(4) + 1

= (x +
(3)/(2) )² -
(5)/(4)

User VinhNT
by
5.5k points